Pharmaceutical Composition of a Topical Dosage form of Itraconazole for the Treatment of Athlete's Foot - Akshi, Garg; Jitender, Madan (International Journal of Psychosocial Rehabilitation, 2019)
Athlete’s foot is a cutaneous fungal infection that usually begins between the toes. It usually happens in people whose feet are very sweaty while confined in fitting shoes. Signs and symptoms of the athlete’s foot include a scaly rash which usually causes “itching, stinging and burning”. It is caused by the fungus "Trychophytonrubrum". In severe cases, the skin may blister (A collection of fluid below the top layer of skin i.e. epidermis). Many oral and topical treatments are available to cure Athlete's foot. Oral itraconazole (Mw~705.64 g, Melting Point~166.3°C, Weak base pKa~3.7) is the most commonly used antifungal drug in the treatment of Athlete's foot at the dose of 100 mg once-a-day for 30 days. The anti-fungal drug itraconazole is used to treat fungal infections in adults. Infection of the lungs, mouth or throat, toenails or fingernails includes infections in any part of the body. Some of the brands of itraconazole cannot be used for the treatment of fungal infections of the fingernails or toenails. Mechanistically, itraconazole inhibits the fungal-mediated synthesis of ergosterol, via inhibition of lanosterol 14α-demethylase. However, poor physicochemical attributes, interference of food, side-effects (Nausea, diarrohea, and hepatotoxicity) and lesser bioavailability (55%) alters the therapeutic efficacy of itraconazole. in present investigation, a pharmaceutical dermal cream of itraconazole was formulated by oil in water (O/w) emulsion method to improve skin penetration in the treatment of tineapedis infection. Among several chemical permeation enhancers, dimethyl sulfoxide was used in the pharmaceutical dermal cream of itraconazole to augment the penetration of drug in skin.